An in silico network pharmacology and molecular dynamics simulations study of engeletin in ischemic stroke with computational prioritisation of NOS2 - Manga Devi Chinta; Santhrani Thakur (Creative Pharma Assent, 2026)
Background: Engeletin, a polyphenolic flavonoid, has demonstrated neuroprotective effects in experimental stroke models. However, the molecular interactome underlying its multitarget actions in ischemic stroke remains insufficiently characterized. Methodology: An integrated in silico workflow was applied to identify stroke-relevant targets of engeletin, combining target prediction, protein–protein interaction analysis, GO and KEGG pathway enrichment, and engeletin–target–pathway network construction. Network topology metrics were used to prioritize targets for downstream structure-based analyses. Docking was performed on short-listed targets, and selected protein–ligand complexes were further evaluated using molecular dynamics (MD) simulations to assess binding stability. In silico ADME profiling was conducted to contextualize translational considerations. Results and Discussion: Nineteen targets were identified through a confidence-driven overlap strategy. Degree-based network filtering short-listed 11 targets for docking. Multi-centrality convergence across protein–protein interaction and engeletin–target–pathway networks prioritized six influential hubs (PTGS2, CASP3, NOS2, MMP9, JAK2, and EGFR) implicated in inflammatory, apoptotic, and vascular regulation. Functional enrichment analyses highlighted interconnected inflammatory–immune, vascular, and metabolic stress pathways, with KEGG pathways interpreted as nominally enriched. Docking and MD analyses differentiated dynamically stable interactions from network-level co-modulated hubs, with engeletin exhibiting the most stable binding to NOS2 (inducible nitric oxide synthase). Conclusion: Integration of network pharmacology with structure-based analyses prioritizes NOS2-centered modulation and relaxin-associated vascular signaling as testable mechanisms for future experimental validation of engeletin in ischemic stroke.